In Situ Verification of Tendons of First Segmental Post-Tensioned Road Bridges - Kralovanec Jakub; Moravcik Martin; Zahuranec Michal; Bahleda Frantisek (Civil and Environmental Engineering)
Prestressed concrete bridges represent a massive part of our infrastructure. The state of the prestressing is crucial for the load-bearing capacity and remaining service life of these structures. Harmful factors, for instance, corrosion negatively affect the prestressing steel and consequently the level of prestressing. The risk of corrosion is higher if the ducts are not injected (or partially injected) by cement grout. Therefore, the detection of the state of the prestressing steel is an important part of the diagnostic survey which should be performed on existing prestressed concrete structures. This paper describes the outcomes of a diagnostic survey performed on four segmental post-tensioned road bridges built in the 1970s. Specifically, one single-span bridge, one three-span bridge, and two two-span bridges are pivotal objects of this study. These bridges’ prestressing has been assessed and the outcomes have been evaluated with final recommendations for the administrator. To sum up, the prestressing of assessed bridges was in relatively good condition with none or only local corrosion. Consequently, the overall prestressing level should not be hugely affected, but certain actions from the administrator are required to repair detected failures and extend service life.